The insurance market in Poland - an analysis of the current situation and development prospects - Borda, Marta; Ronka-Chmielowiec, Wanda (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The paper contains an analysis of changes which took place on the Polish insurance market during the last twenty years. First, some important facts concerning the development of this market between 1990 and 2009 are briefly described. Then, the results of research concerning development tendencies, threats and comparisons with other foreign markets are presented. The development ratios characterizing the insurance market in Poland in comparison with developed markets is analysed. The conducted analysis was mainly focused on the following areas: market structure measured with gross written premium and claims paid, number of insurers operating on the market, ownership and capital structure of the insurance companies and insurance distribution channels. Moreover, new trends concerning changes in demand for insurance products and the increasing need for financial insurance, private health insurance and liability insurance are considered. In the last part of the paper, conclusions and development opportunities as well as new challenges for the insurance sector in Poland are discussed.
Mathematical Economics, 2011, Nr 7 (14), s. 19-30
Keywords: insurance; development; analysis; market structure; insurance products; insurance companies